2004
DOI: 10.1097/01.ju.0000125340.84492.a7
|View full text |Cite
|
Sign up to set email alerts
|

Adrenal Metastases in 1,635 Patients With Renal Cell Carcinoma: Outcome and Indication for Adrenalectomy

Abstract: Adrenal metastases from primary renal cell carcinoma were found significantly more often in patients with advanced tumor stages. Ipsilateral adrenalectomy should be recommended for all resectable renal cell carcinoma with a primary tumor of greater than 4 cm or with nonorgan confined tumor stages (T3 or greater) since a false-negative rate of about 20% can be expected with current imaging techniques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
59
0
5

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(67 citation statements)
references
References 13 publications
2
59
0
5
Order By: Relevance
“…This compares with survivals of 19 and 16% for patients with combined adrenal and extraadrenal metastatic spread of tumor. 93 Microscopic invasion of the renal vein was omitted from the 1987 edition of the TNM classification and vascular involvement was grouped according to invasion of the renal vein or the vena cava (T3b). In 1997, the T3b category was further subdivided into tumor extending into renal vein or the vena cava below the diaphragm (T3b) or into vena cava above the diaphragm (T3c).…”
Section: Regional Spread Of Tumor (Tnm Category T3)mentioning
confidence: 99%
“…This compares with survivals of 19 and 16% for patients with combined adrenal and extraadrenal metastatic spread of tumor. 93 Microscopic invasion of the renal vein was omitted from the 1987 edition of the TNM classification and vascular involvement was grouped according to invasion of the renal vein or the vena cava (T3b). In 1997, the T3b category was further subdivided into tumor extending into renal vein or the vena cava below the diaphragm (T3b) or into vena cava above the diaphragm (T3c).…”
Section: Regional Spread Of Tumor (Tnm Category T3)mentioning
confidence: 99%
“…Open radical nephrectomy was the standard curative intervention for localised RCC for the past five decades [2]. Furthermore, there were controversies over whether radical nephrectomy should be performed in conjunction with ipsilateral adrenalectomy as originally described by Robson, or if the adrenal should be preserved [3][4][5][6] and whether ipsilateral extended retroperitoneal lymphadenectomy or limited hilar lymphadenectomy should be performed [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…20 Open surgical Several series confirm that surgical management of a metastatic adrenal lesion does improve survival in select patients and can lead to potential cure. 19,[22][23][24][25][26][27][28][29][30][31][32] In a series reported by Higashiyama et al, lung cancer patients with isolated metastatic disease to the adrenal gland who underwent surgical resection followed by adjuvant chemotherapy or radiotherapy fared much better than patients treated non-operatively. 27 This study demonstrated a median survival of less than 6 months for patients treated medically, and survival benefit of greater than 9 months in the surgical group, with one patient showing no disease progression after 40 months.…”
Section: Surgical Management Of Adrenal Metastasismentioning
confidence: 99%
“…30 Siemer et al examined renal cell cancer patients and noted that patients with a solitary adrenal metastasis achieved a significant tumor-specific survival benefit with a median survival of 68 months compared to a median survival of 10 months in those patients with additional metastatic foci. 25 Risk factors such as the site of the primary cancer, size, histology, primary tumor type (adenocarcinoma possibly being more favorable), presence of other distant metastases, local invasion, and a lengthy disease-free interval after initial diagnosis appear to impact on cancer survival, but these risk factors have been somewhat variable. 4,[25][26][27][28][29][30][31][32][33] The optimal surgical approach for adrenalectomy for metastatic (median survival, 21 months).…”
Section: Surgical Management Of Adrenal Metastasismentioning
confidence: 99%
See 1 more Smart Citation